2023
DOI: 10.3390/cancers15153849
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immune Microenvironment in Gynecologic Cancers

Daniel Margul,
Camilla Yu,
Mariam M. AlHilli

Abstract: Gynecologic cancers have varying response rates to immunotherapy due to the heterogeneity of each cancer’s molecular biology and features of the tumor immune microenvironment (TIME). This article reviews key features of the TIME and its role in the pathophysiology and treatment of ovarian, endometrial, cervical, vulvar, and vaginal cancer. Knowledge of the role of the TIME in gynecologic cancers has been rapidly developing with a large body of preclinical studies demonstrating an intricate yet dichotomous role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 164 publications
0
1
0
Order By: Relevance
“…As a chemokine, CCL20 helps to prevent infection, hemostasis, cell proliferation, and remodeling. It also attracts antigens in the form of delivery cells, such as Langerhans cells, to the virus-infected area 34 . Immunoin ltrating data showed that telomere core genes associated with cervical cancer were associated with Mast cells resting, Dendritic cells resting, T cells regulatory (Tregs), T cells CD8, Mast cells activated, Macrophages, Neutrophils, B cells memory, T cells gamma delta, Monocytes and other immune cells were signi cantly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…As a chemokine, CCL20 helps to prevent infection, hemostasis, cell proliferation, and remodeling. It also attracts antigens in the form of delivery cells, such as Langerhans cells, to the virus-infected area 34 . Immunoin ltrating data showed that telomere core genes associated with cervical cancer were associated with Mast cells resting, Dendritic cells resting, T cells regulatory (Tregs), T cells CD8, Mast cells activated, Macrophages, Neutrophils, B cells memory, T cells gamma delta, Monocytes and other immune cells were signi cantly correlated.…”
Section: Discussionmentioning
confidence: 99%